Supporting Autonomous Learning: How Effective Are Online Tutors? - Kaur, Abtar; Mansor Fadzil,; Ansary Ahmed, (2005)
The emergence of the World Wide Web and related technologies has encouraged many higher learning institutions to include online classroom characteristics into the learning process. At the Open University Malaysia (OUM), online learning forms a crucial element in achieving institutional aims and learning philosophy. Being distanced from the physical campus, OUM students are expected to be autonomous. But physical autonomy demands the institution to provide the challenge for mental autonomy and online learning is one such channel. In a research and subsequent issue of "How effective are online tutors?" a total of 2851 postings were analysed using the following rubrics: motivation, communication, engaging the learner, knowledge building, encouraging higher-order thinking, collaborative online learning and technology support. Findings showed that OUM tutors are adequately supportive in motivating and communicating with students but need to pay particular attention all other areas. (Authors' abstract)